Epidemiological and clinical characteristics of hospitalized pediatric patients with Mycoplasma pneumoniae pneumonia before and after the COVID-19 pandemic in China: a retrospective multicenter study - Yuqian Zhang; Chenglei Su; Yang Zhang; Shuo Ding; Xianliang Yan; Jianguo Zhang; Zhimin Tao (BMC Infectious Diseases)
Abstract Background In China many respiratory pathogens stayed low activities amid the COVID-19 pandemic due to strict measures and controls. We here aimed to study the epidemiological and clinical characteristics of pediatric inpatients with Mycoplasma pneumoniae pneumonia (MPP) after the mandatory COVID-19 restrictions were lifted, in comparison to those before the COVID-19 pandemic. Methods We here included 4,296 pediatric patients with MPP, hospitalized by two medical centers in Jiangsu Province, China, from January 2015 to March 2024. Patients were divided into the pre-COVID (n = 1,662) and post-COVID (n = 2,634) groups. Their baseline characteristics, laboratory test results and radiological patterns were separately assessed and compared between the two groups to determine the substantial changes in the disease profile of MPP after the COVID-19 pandemic. Results Epidemiological results suggested a higher annual incidence of MPP after the COVID-19 pandemic when the outbreak reached a peak in October, two months delayed in seasonality compared to that in the pre-COVID era. For pediatric patients with MPP, there was no difference in their median ages, gender ratios, and severe case percentages between the two groups, where most patients were younger than 14 years old. With significance, the post-COVID group had more occurrences of cough and expectoration and higher incidences of influenza A/B virus (IAV/IBV) co-infection than the pre-COVID group. Many hematological parameters and radiological features between the two groups displayed alteration, but comparatively there demonstrated no worsened severity in hospitalized children with MPP after COVID-19 pandemic. Concurrently, the post-COVID group was administered with fewer antibiotics but more corticosteroids for effective treatment than the pre-COVID group. Conclusion Through the COVID-19 pandemic, the epidemiological and clinical characteristics of pediatric patients with MPP differed, but there was no evident change in the disease severity. After the COVID-19 pandemic, the increased incidence of IAV/IBV co-infection may contribute to the differences in clinical symptoms and hematological profiles, while the adding usage of corticosteroids might treat more effectively.